(untitled) (Journal of University of Babylon for Engineering Sciences, 2020)
Thin films science and technology plays an important role in the high-tech industries. Thin film technology has been developed primarily for the need of the integrated circuit industry. The demand for development of smaller and smaller devices with higher speed especially in new generation of integrated circuits requires advanced materials and new processing techniques suitable for future giga scale integration (GSI) technology.one of the most significant application of thin film is the touch screen, Thus, knowledge and determination of the nature, functions and new properties of thin films can be used for the development of new technologies for future applications. This research presents the principle of the thin-layer approximation in direct current conduction problems. The approximation presented in this research is not limited to direct current problems: it can also use it for modeling of diffusion, heat conduction, flow through porous media using Darcy’s law, and other types of physics that the divergence of a gradient flux describes. By applied the model it was determined , the total current density through the thin film, 5 slice for the current density across the thin film ,the variation of electric potential(V) with respect to current density through the thin film and the behavior of electric field through the region of thin film.